Labor savings in agriculture and inequality at different spatial scales: The expansion of oil palm in Indonesia - Christoph Kubitza; Jonida Bou Dib; Thomas Kopp; Vijesh V. Krishna; Nunung Nuryartono; Matin Qaim; Miriam Romero; Stephan Klasen (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2019)
Labor saving innovations are essential to increase agricultural productivity, but they might also increase inequality through displacing labor. Empirical evidence on such labor displacements is limited. This study uses representative data at local and national scales to analyze labor market effects of the expansion of oil palm among smallholder farmers in Indonesia. Oil palm is labor-saving in the sense that it requires much less labor per unit of land than alternative crops. The labor market effects depend on how oil-palm-adopting farm households reallocate the saved labor time; either to the off-farm sector or to cultivating additional land. If adopters increase their labor supply to the off-farm sector, employment and wages of rural laborers might decrease. This is especially true for female agricultural laborers, who are often employed in alternative crops but less in oil palm, as their labor productivity in this particular crop is lower than that of men. However, our results suggest that oil palm adoption in Indonesia largely led to the cultivation of additional land, entailing higher agricultural labor demand, especially for men. At the same time, the oil palm boom caused broader rural economic development, providing additional employment opportunities also in the non-agricultural sector, thus absorbing some of the female labor released from agriculture. Overall employment rates did not decrease, neither for men nor for women. While this is good news from economic and social perspectives, the cropland expansion contributes to deforestation with adverse environmental effects. Policies to curb deforestation are needed. Forest conservation policies should go hand-in-hand with measures to further improve rural non-agricultural employment opportunities, to avoid negative socioeconomic effects for poor rural laborers, and women in particular.
urn:nbn:de:gbv:7-webdoc-3991-2
Keywords: Q23; R14; J61; 330; tree-planting; oil palm; intentions; mediation; Asia